Transgender and Gender Nonconforming Youths' Emotions: The Appraisal, Valence, Arousal Model. (January 2021) - Budge, Stephanie L.; Orzechowski, Maria; Schams, Samantha; Lavender, Amy; Onsgard, Kate; Leibowitz, Scott; Katz-Wise, Sabra L.
Increased scientific understanding explains why transgender and gender nonconforming (TGNC) youth report more mental health concerns than their cisgender peers. However, the emotional processes of TGNC youth have not been assessed beyond mental health diagnoses. Our aim in this study was to investigate how TGNC youth understand, experience, and label their emotional experiences. We conduced a two-tiered qualitative analysis of 20 predominantly White TGNC youths, ages 7–18 years, resulting in the creation of the appraisal, valence, arousal theory of emotions. Within the theory, emotions are categorized in four quadrants: Reflective/Unpleasant, Anticipatory/Unpleasant, Reflective/Pleasant, and Anticipatory/Pleasant. Results indicated that the majority of TGNC youths' emotions were located in the Reflective/Unpleasant and Reflective/Pleasant quadrants. The current study highlights TGNC youths' appraisal of emotions and the potential impact on youths' cognitive and emotional processes. Interventions should attend to pleasant and unpleasant aspects of emotions while also focusing on youths' understanding of the context of their emotions.